Do Quilombo Sítio Veiga à Universidade: uma experiência extensionista antirracista no Sertão Central cearense - Silva, Cristiane Sousa da (2018)
The present thesis has as main objective to analyze the extensionist actions of the Multidisciplinary Nucleus in Quilombola Teaching (Numeq) and its contribution to an antiracist education in private higher education in Quixadá-CE. And as specific objectives have: to promote the training of students and teachers on the historical, cultural and social re-signification of the black and quilombola population in Brazil; to recognize the relevance of the racial question in the academy as well as to contribute to the construction of new knowledge in the practice of teaching and learning; to know the history and culture of Quilombo Sítio Veiga and transform it into knowledge to be worked in private higher education; contribute to the valorization and visibility of racial issues in private higher education in the areas of human, exact and health. The methodology used was of a qualitative nature with a focus on intervention research, the constitution of the field of intervention took place in the higher education of private network located in the Central Hinterland of Ceará, in the city of Quixadá. For the composition of the sample were inferred 5 teachers/ and 18 students participating in the 6 courses involved in Numeq in the period 2015.1 and 2015.2. As a research technique in order to collect the data, we opted for participant observation that allowed the effective participation of the researcher in the group, both in the training meetings and in the interventions in the quilombo community Sítio Veiga. And the second instrument we prioritized was the questionnaire aimed at evaluating students and teachers‟ views on race before and after intervention research. To interpret the data collected in the field research, we used the technique of content analysis to interpret the data collected in the questionnaires, the categories emerged from the responses of those involved in this investigation, which were: Numeq and the dialogue with the teachers and students: Experiences, looks and understanding; Numeq and contributions to an anti-racist academic formation. From the results, it could be noted that, in the first category, Numeq allowed the students and teachers to have a broad vision and a political and historical awareness about the oppressions, more specifically on racism. Regarding the second category – Numeq and contributions to an anti-racist academic formation –, it is important to place the racial theme at the heart of the debate in an interdisciplinary bias through the relationship theory and practice in the quilombo, as well as to bring to the fore voices and silenced and hidden images of the curriculum through these extensionist actions.